If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 4 + -1e = 2 Combine like terms: 4 + 4 = 8 8 + -1e = 2 Solving 8 + -1e = 2 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1e = 2 + -8 Combine like terms: 8 + -8 = 0 0 + -1e = 2 + -8 -1e = 2 + -8 Combine like terms: 2 + -8 = -6 -1e = -6 Divide each side by '-1'. e = 6 Simplifying e = 6
| 68+65+x+x= | | 5x+5=10x-3 | | -10x^2+50x+12=0 | | 3n+5x=6 | | .5(8*12)= | | 1/2(2x-5)=3 | | .5(10*12.8)= | | -16X^2+4X+20=0 | | 14x+35=(4x-9)-x | | 10(12.8)= | | 4x+28=13x-93 | | 11x-11=100 | | 9(t+1)=81 | | 3(H+5)=22 | | -2=v-6+3 | | 7x+8/2+4x-3/6=34 | | 0=(1/5)x+2 | | e-5+7=2 | | e/5+7=4 | | 16+3/4x=7 | | 3x^(4/3)+3=51 | | 2/d+1/4=11/12 | | 3x=(124+1676+3600)/2x | | (5a^2)-(6a)-32=0 | | 2x+8=-13x-22 | | -18(d-989)+2=560 | | 19-r=81 | | 5x+4y=11fory | | 4(z-85)=56 | | (x^2+2x)/(2x^3+10x^2+12x) | | 83-w=86 | | 73=62-u |